The evolution of virulence in Pseudomonas aeruginosa during chronic wound infection. Issue 1937 (21st October 2020) - Vanderwoude, Jelly; Fleming, Derek; Azimi, Sheyda; Trivedi, Urvish; Rumbaugh, Kendra P.; Diggle, Stephen P.
Abstract : Opportunistic pathogens are associated with a number of chronic human infections, yet the evolution of virulence in these organisms during chronic infection remains poorly understood. Here, we tested the evolution of virulence in the human opportunistic pathogen Pseudomonas aeruginosa in a murine chronic wound model using a two-part serial passage and sepsis experiment, and found that virulence evolved in different directions in each line of evolution. We also assessed P. aeruginosa adaptation to a chronic wound after 42 days of evolution and found that morphological diversity in our evolved populations was limited compared with that previously described in cystic fibrosis (CF) infections. Using whole-genome sequencing, we found that genes previously implicated in P. aeruginosa pathogenesis ( lasR, pilR, fleQ, rpoN and pvcA ) contained mutations during the course of evolution in wounds, with selection occurring in parallel across all lines of evolution. Our findings highlight that: (i) P. aeruginosa heterogeneity may be less extensive in chronic wounds than in CF lungs; (ii) genes involved in P. aeruginosa pathogenesis acquire mutations during chronic wound infection; (iii) similar genetic adaptations are employed by P. aeruginosa across multiple infection environments; and (iv) current models of virulence may not adequately explain the diverging evolutionary trajectories observed in an opportunistic pathogen during chronic wound infection.